Reframing difference in organizational communication studies research, pedagogy, and practice - Mumby, Dennis K. (Thousand Oaks, Calif. ; London : SAGE, 2011)
All of the scholars in this volume explore difference from a variety of perspectives, each of which systematically looks at the relationships among communication, organizing, and difference.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Communication in organizations; Organizational behavior